(untitled) (Bulletin of the International Association for Paleodontology, 2021)
This paper describes a dental anomaly called talon cusp from Gilimanuk Prehistoric site. Indonesia. The dating of the site is between 750 BC to 900 AD. This anomaly located in lateral incisors of individual LVI. The individual described as a woman and her age at death were 35-40 years old. The first evidence of Talon cusp in a permanent tooth from the Indonesian archaeological context was never been reported before which makes this anomaly is unique. The etiology of talon cusp is still uncertain.